Current scenario of marker-assisted selection in breeding of minor oilseed crops of India: CURRENT SCENARIO OF MARKER-ASSISTED SELECTION IN BREEDING OF MINOR OILSEED CROPS - P KADIRVEL; CH ANIL KUMAR; P S BASAVARAJ; S GEETHANJALI; Y RUSHWANTH REDDY; V DINESH RAHUL; S SENTHILVEL (Journal of Oilseeds Research, 2021)
Sunflower, safflower, castor, sesame, linseed and niger are theminor oilseed crops having potential to contribute towards achieving self-sufficiency in vegetable oil production in India. Decades of breeding research have resulted in release of high yielding cultivars with resistance to biotic stresses. However, the productivity levels are stagnated; further improvement in genetic gain requires integration of molecular tools in breeding programmes. Molecular markers, genomics andmarker-assisted selection technologies are widely exploited for improvement of crops. In this review, current status of development and application of molecular markers in the oilseed crops viz., sunflower, castor, safflower, sesame, linseed and niger are presented.